The determinants of export performance: a study on Felda Marketing Sdn Bhd / Mohd Aizzuddin Hares (Faculty of Business and Management, 2008)
Maintaining the standard of living in small open economies requires engaging in international exchange. Export performance has been a central construct in the study of export marketing. Several studies have attempted to identify organizational and managerial antecedents of export performance and assess the relative importance of these antecedents. This research was done to find what the determinants of export performance are in the context of a Malaysian firm. Felda Marketing Services Sdn Bhd was chosen as tne company of research. The objective was to examine the trend the export of palm oil products over a period of 5 years from 2003-2007 and also to examine the determinants of export performance for Felda Marketing Services Sdn Bhd. These findings are important because it can help the management make decisions on export oriented activities. The results of the findings were regressed using ordinary least square method and findings were presented through tables and graphs.